Ponto-Caspian mysid shrimp Paramysis lacustris has reached the Elbe estuary - Christine Schottmüller; Natascha Holl; Frank Suhling; Boris Schröder; C. Gabriel David (Scientific Reports)
Abstract As part of monitoring conducted alongside a river engineering project, the Ponto-Caspian mysid shrimp Paramysis lacustris (P. lacustris) was detected for the first time in the tidal Elbe in August 2023. Alongside P. lacustris, a second Ponto-Caspian mysid species, Limnomysis benedeni (L. benedeni), was also identified. The previous year’s investigation yielded no records of these mysids, suggesting that the species, last observed in 2019 in the Havel River in Saxony-Anhalt, are currently expanding into the tidal Elbe. In addition to addressing sampling aspects, we present the dispersal pathway of P. lacustris since its first recorded observation in 1882 and discuss the probable impact of the newly found species in the river Elbe based on former findings.